Комплексна механізація виробництва молока з модернізацією кормозбирального комбайна - Якименко, Наталія Григорівна; Yakymenko, Nataliia (ЦНТУ, 2023)
Вдосконалено технологію виробництва молока шляхом модернізації кормозбирального комбайна. Змінено структуру стада у відповідності до вимог інтенсивної технології. Проведено вдосконалення привода жатки для збирання трави. У результаті модернізації зменшено масу жатки та підвищено якість кормів . Проведені технологічні, кінематичні і енергетичні розрахунки, обґрунтовані геометричні і конструктивні параметри вузлів і даталей привода жатки. Проведений аналіз небезпечних і шкідливих факторів та запропоновано заходи по створенню нормальних та нешкідливих санітарно-гігієнічних умов праці. The technology of growing winter wheat has been improved by using a unit for pre-sowing processing based on cylindrical drums with pointed teeth. The operational and technological map of the pre-sowing treatment of the foundation was calculated and compiled. The unit for pre-sowing soil preparation has been modernized. As a result of modernization, the unit destroys weeds, levels the surface of the field and finally loosens the foundation layer at the depth of wrapping. Technological, kinematic and energy calculations were carried out, the geometric and structural parameters of the first external drum were substantiated. An analysis of dangerous and harmful factors is carried out and we offer measures to create normal and harmless sanitary and hygienic working conditions.
Complex mechanization of milk production with modernization of the forage harvester
Keywords: озима пшениця; передпосівний обробіток ґрунту; барабан; winter wheat; pre-sowing treatment of the base; drum